2014
DOI: 10.1166/jpsp.2014.1022
|View full text |Cite
|
Sign up to set email alerts
|

Ets Related Gene and Smad3 Proteins Collaborate to Activate Transforming Growth Factor-Beta Mediated Signaling Pathway in ETS Related Gene-Positive Prostate Cancer Cells

Abstract: TGF-β/Smads signaling plays a significant role in the regulation of growth of normal and prostate cancer cells. Smad proteins function as important mediators of intracellular signal transduction of transforming growth factor-β (TGF-β). TGF-β signaling pathway is known to regulate cell proliferation, differentiation, apoptosis and play a major role in some human diseases and cancers. Following their phosphorylation by TGF-β receptor-I, Receptor-regulated Smads (including Smad2 and Smad3 proteins) form a heterom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…We demonstrate that ERG directly represses SMAD2/3 transcriptional activity, independently of expression of SMAD2/3 or its receptor ALK5. We find that ERG can interact with SMAD2/3 in HUVEC and in HSEC in agreement with studies that show overexpression of exogenous ERG and SMAD3 results in protein interaction 36, 37 . ERG and SMAD3 both bind to the promoters of target genes, indicating that ERG acts as a co-repressor for SMAD3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrate that ERG directly represses SMAD2/3 transcriptional activity, independently of expression of SMAD2/3 or its receptor ALK5. We find that ERG can interact with SMAD2/3 in HUVEC and in HSEC in agreement with studies that show overexpression of exogenous ERG and SMAD3 results in protein interaction 36, 37 . ERG and SMAD3 both bind to the promoters of target genes, indicating that ERG acts as a co-repressor for SMAD3.…”
Section: Discussionsupporting
confidence: 92%
“…Cells were collected in lysis buffer (50 mM Tris, pH 7.5, 150 mM NaCl, 0.1% Igepal, 1 mM EDTA, 0.25% sodium deoxycholate) 37 supplemented with 1 mM phenylmethylsufony fluoride (PMSF), protease inhibitor cocktail, and phosphatase inhibitor cocktail 2 and 3 (Sigma). Endonuclease treatment was conducted with the addition of 500 units of Benzonase (Sigma-Aldrich, UK) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that about 50% of all prostate cancers carry a gene fusion linking the androgen-regulated serine protease TMPRSS2 with the ETS-transcription factor ERG resulting in an androgen-related overexpression of ERG with subsequent transcriptional deregulation of more than 1600 ERG target genes [21] , [43] , [44] . Others and we have shown that activation of the TGF-ß signaling pathway is one important consequence of ERG fusion in prostate cancer [44] , [45] , [46] . That the extracellular matrix modulator TGF-β1 is an important stimulator of BGN transcriptional and post translational modifications [47] , [48] provides a mechanistic explanation for the higher fraction of cancers with BGN up-regulation in ERG-positive as compared to ERG-negative cancers.…”
Section: Discussionmentioning
confidence: 72%
“…This implies that ETV1 overexpression restrains its own oncogenic impact, at least during the initial PIN phase of prostate tumorigenesis, by causing SMAD3/4 overexpression. Although we have not investigated the mechanism, one speculation is that interaction with ETV1 might stabilize SMAD proteins, similar as has been observed for SMAD3 and another ETS transcription factor, the ERG oncoprotein 46 . However, in contradiction to this hypothesis, we observed no alteration of SMAD3/4 protein levels in PC3 prostate cancer cells upon ETV1 downregulation (see Fig.…”
Section: Discussionmentioning
confidence: 80%